MODEL PEMBELAJARAN PROJECT BASED LEARNING DALAM MENGEMBANGKAN KREATIFITAS SISWA SEKOLAH DASAR - Ahmad Faozan; Sutrisna Wibawa (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Citizenship Education Learning (PKN) is a subject that aims to shape the character of students so that they have understanding, attitudes and skills as good and responsible citizens. There is a need for activities or learning models to achieve these goals. The Project Based Learning learning model is the choice of researchers to improve skills and creativity in PKN learning. This article aims to explain the Project Based Learning learning model in increasing the creativity of class V students at Kaweden State Elementary School. This type of research is descriptive qualitative with research subjects as many as 21 students. Data collection techniques use observation techniques, creative attitude observation rubrics, interviews and documentation. Meanwhile, to examine the data using the Milles and Huberman analysis technique which consists of data reduction, data presentation and drawing conclusions. The research results show that the project based learning model is able to increase student creativity. Students are able to produce innovative works.